Pro Drupal 7 development - Tomlinson, Todd.; VanDyk, John K. ([Berkeley, Calif.] : Apress ; New York, NY : Springer [distributor], 2010)
Provides information on using the open source content management framework to create Web sites.
Includes bibliographical references and index.
Keywords: Drupal (Computer file); Drupal (Computer software); Web site development; Web sites -- Design